2017
DOI: 10.1371/journal.pone.0186787
|View full text |Cite
|
Sign up to set email alerts
|

Motor skill delays in pre-school children with leukemia one year after treatment: Hematopoietic stem cell transplantation therapy as an important risk factor

Abstract: CNS-directed therapies for the treatment of leukemia can adversely affect the acquisition of new skills, such as reading/writing and math. Two years after the end of treatments, children show gross and fine motor skill delays that may persist even when patients are considered healed. The goal of the present study was to assess motor skills difficulties in pre-school children with leukemia one year after treatment. Particular attention has been paid to those patients who had undergone Hematopoietic Stem Cell Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Possible interventions could focus on two directions: the first could be the implementing of motor skills functioning on children with cancer both during the treatment phase, when the therapies impacted negatively on their motor performance (Taverna et al., ), and also when they were off therapies, adopting a specific rehabilitative programme and paediatric occupational therapy to reduce their fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Possible interventions could focus on two directions: the first could be the implementing of motor skills functioning on children with cancer both during the treatment phase, when the therapies impacted negatively on their motor performance (Taverna et al., ), and also when they were off therapies, adopting a specific rehabilitative programme and paediatric occupational therapy to reduce their fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effectiveness of handwriting intervention programs found improvements in fine motor and visual-motor skills in children receiving direct occupational therapy lasting seven or more months [33][34][35][36]. Nevertheless, research has suggested that even short-term interventions targeting fine motor performances in children of lower elementary school ages can lead to significant changes in individuals with or without disabilities [37][38][39][40][41][42]. Furthermore, short-term interventions can be more easily managed and would offer the possibility to be included also in the educational curriculum to improve handwriting foundational skills in preschool children.…”
Section: Intervention Programs Duration and Gender Differencesmentioning
confidence: 99%
“…32 Two studies indicated that the correlation coefficients between the side effects of cancer treatment and physical activity and between physical activity and quality of life for children with hematologic cancer were -0.33 and 0.66, respectively. 33,34 With reference to the guideline proposed by Cohen, the aforementioned correlation coefficients were arranged from small to large effect sizes (r), and the necessary sample size of this study was calculated using the smallest effect size. 35 An effect size at a 5% significance level (p <0.5) and a power of 0.8 was used to predict the difference between the hematologic cancer group and the healthy group.…”
Section: Subjectsmentioning
confidence: 99%